The Diverse Banking Products as a Tool for Achieving Financial Inclusion : Array - Olunuga, Adeshola; Agbesuyi, Olusegun (The Journal of Accounting and Management, 2021)
This paper presents recent research on diverse banking products on achieving financial inclusion. Financial inclusion particularly in developing countries has become worrisome as majority of rural dwellers still lack access to formal financial services. However, financial inclusion is central to poverty alleviation and sustainable economic growth. The study employed questionnaire survey and observation to gather information from bank managers and customers of selected bank. The techniques were additionally enhanced with a semi-structured interview with bank managers and customers. The obtained data were analyzed by statistical methods. In association with the conducted researches it can be generally stated that the respondents concur with the statement that diverse banking products influence financial inclusion. The study concluded that a strong financial system typically must promote credit and diverse banking products to consumers which invariably promote economic growth. Simultaneously, this enhances quality of life of the people, as well creates and invigorates new jobs